Mengintegrasikan agama Islam pada pembelajaran matematika - Maulida, Ilvi Nur Diana (Maliki Interdisciplinary Journal, 2024)
Mentioning the terms integration of mathematics and Islam is actually not quite appropriate, because basically Islam does not resolve religion and science (mathematics), both are interrelated and need to be studied hand in hand. There is no discrepancy between religion and science. In order to achieve a fusion of mathematics and religion, it is important to use Islamically compatible methods. Finding theological justification for mathematics alone is not enough, and there has been no attempt to Islamize mathematics. As with other learning, mathematics learning must continue to develop in terms of quality and quality to meet efforts to improve optimal learning outcomes. This effort must be carried out creatively and innovatively following the development of the times, increasingly sophisticated and modern technology.Mentioning the terms integration of mathematics and Islam is actually not quite appropriate, because basically Islam does not resolve religion and science (mathematics), both are interrelated and need to be studied hand in hand. There is no discrepancy between religion and science. In order to achieve a fusion of mathematics and religion, it is important to use Islamically compatible methods. Finding theological justification for mathematics alone is not enough, and there has been no attempt to Islamize mathematics. As with other learning, mathematics learning must continue to develop in terms of quality and quality to meet efforts to improve optimal learning outcomes. This effort must be carried out creatively and innovatively following the development of the times, increasingly sophisticated and modern technology.